Ceratite pigmentar ou ceratopatia pigmentar em pug? relato de caso. - Lima, Pedro Luiz Sandes de. (2019)
The corneal pigmentation in dogs is a common clinical finding that can have numerous causes such as eyelash and eyelid diseases, shallow eye orbit and tear quantity or quality deficiency, or, simply, have a hereditary etiology in Pugs. All these factors lead to chronic keratitis and as a consequence the pigmentation of the epithelium and stroma corneal occur. This study aims to report a case of a Pug with corneal pigmentation, exuberant nasal folds and medial corner entropio. The main diseases of the eye attachments and surgical techniques of the treatment were discussed here. It was not possible conclude that the corneal pigmentation were strictly related to the eye attachments disorders or to the breed genetic predisposition.